If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1(x * x + 7) = -35 Multiply x * x 8 + -1(x2 + 7) = -35 Reorder the terms: 8 + -1(7 + x2) = -35 8 + (7 * -1 + x2 * -1) = -35 8 + (-7 + -1x2) = -35 Combine like terms: 8 + -7 = 1 1 + -1x2 = -35 Solving 1 + -1x2 = -35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x2 = -35 + -1 Combine like terms: 1 + -1 = 0 0 + -1x2 = -35 + -1 -1x2 = -35 + -1 Combine like terms: -35 + -1 = -36 -1x2 = -36 Divide each side by '-1'. x2 = 36 Simplifying x2 = 36 Take the square root of each side: x = {-6, 6}
| .22(x+6)=.2x+5.3 | | x/3-9/4=x/6-1/2 | | 5v^2-17v=-6 | | 1/x=4/12 | | 8a-12=4(a-5) | | 6n^2+31n+18=0 | | 70m^2-73m+20= | | 2(x-8)=9 | | -2/3x=28 | | Q=j+jet | | X+78=x+41 | | -8=-2z+-14 | | 5y-6y+y+36=6y+30-2y | | 2u+6v=9 | | -3/4x=8/16 | | (255/256)/n | | √5/81 | | 0.9*x=180 | | 8x-3(x-1)=8x+21-2x | | -x-15+9x=3x+2+4y | | M/-4=1/16 | | 2y+3=4y+6 | | 3a+4b-2a+a+6b= | | 4x+4-2x=-2(3x-3) | | X-1/2=-7 | | 3sinx+6=7 | | (3x^2+2xy-y^2)+3x-y=0 | | 12y-30= | | 3t+5=15t+5 | | 3sinx+6=0 | | x/3=2/18 | | 6y-5(y-6)+1=9 |